This I Believe - Kohn, Lucile (Tufts Archival Research Center, 2006)
Lucile Kohn describes the spirit of cooperation she finds in her work and in young people and the inspiration she draws from working with and teaching youth and why this gives her faith that there can be a better world in the future.